Benli, Şeyma (2021). A Unique Maqâma in Ottoman Literature: Debate Between a Fluent Woman and an Eloquent Young Husband by Nev‘îzâde Atâyî. İstanbul: Libra Kitap - Seda Kurt (Akademik Dil ve Edebiyat Dergisi, 2026)
This study “Benli, Şeyma (2021). A Unique Maqâma in Ottoman Literature: Debate Between a Fluent Woman and an Eloquent Young Husband by Nev‘îzâde Atâyî. İstanbul: Libra Kitap. 116 p. ISBN: 9786258472141” is the introduction of the book.